1997
DOI: 10.1136/jnnp.62.6.673
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sensory ataxic neuropathy and ophthalmoplegia with oculomotor nerve hypertrophy associated with IgM antibodies against gangliosides containing disialosyl groups.

Abstract: Writer's cramp (n = 10) t 51-6 (9 0) 8-6 (3-9) 1-56 (0l10)*** 1-53 (0-09)*** 9-7 (1-1) ratios of the individual patients were not known, it is hazardous to assess rates of decline in a small cross sectional sample. The results raise some questions. Firstly, there was bilateral reduction of available striatal D2 receptors, whereas the symptoms were unilateral and there was no asymmetry between the hemispheres. Bilateral abnormalities in writer's cramp, have, however, also been found by others.' I This bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…34 Chronic sensory ataxic neuropathy and ophthalmoplegia with oculomotor nerve hypertrophy: Disialogangliosides. 47 Sensory ataxic neuropathy: GQ1bα; 48 fucosyl‐GD1b and GD1b having blood‐group B (IgM). 33 Severe sensory ataxia: GD1a.…”
Section: Antiglycolipid Antibodies In Immune‐mediated Neurological DImentioning
confidence: 99%
See 1 more Smart Citation
“…34 Chronic sensory ataxic neuropathy and ophthalmoplegia with oculomotor nerve hypertrophy: Disialogangliosides. 47 Sensory ataxic neuropathy: GQ1bα; 48 fucosyl‐GD1b and GD1b having blood‐group B (IgM). 33 Severe sensory ataxia: GD1a.…”
Section: Antiglycolipid Antibodies In Immune‐mediated Neurological DImentioning
confidence: 99%
“…Chronic sensory ataxic neuropathy and ophthalmoplegia with oculomotor nerve hypertrophy: Disialogangliosides. 47…”
Section: Antiglycolipid Antibodies In Immune‐mediated Neurological DImentioning
confidence: 99%
“…Neuropathies associated with immunoglobulin M (IgM) antibodies against disialosyl residues have been defined1 2 3 4 5 6 7 8 as either sensory ataxic neuropathy associated with anti-GD1b IgM antibody,9 chronic sensory ataxic neuropathy associated with anti-disialosyl IgM antibodies, or chronic ataxic neuropathy involving ophthalmoplegia, IgM paraprotein, cold agglutinins and disialosyl antibodies (CANOMAD) 10. The most prominent feature of these neuropathies is sensory ataxia with relatively well-preserved muscle strength and small-fibre sensation.…”
mentioning
confidence: 99%
“…In the biopsy specimen, a decrease in large myelinated fibers was not obvious in the sural nerve. Several studies have shown loss of large myelinated fibers of the sural nerve in the neuropathy associated with anti‐disialosyl IgM antibodies, but the biopsy in these cases was performed some 6–25 years after onset 5, 6, 15, 17, 19, 21, 23. A decrease in larger myelinated fibers might therefore be prominent only at such a chronic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathies associated with immunoglobulin M (IgM) antibodies against disialosyl residues have been reported1, 3–6, 12, 13, 15, 16, 19, 21, 23 as a “sensory ataxic neuropathy associated with anti GD1b IgM antibody,”17 a “chronic sensory ataxic neuropathy with anti‐disialosyl IgM antibodies,” or a “chronic ataxic neuropathy, ophthalmoplegia, IgM paraprotein, cold agglutinins and disialosyl antibodies (CANOMAD).”22 The most prominent feature of these neuropathies is sensory ataxia with relative preservation of muscle strength and small‐fiber sensation. The patients in these cases had IgM antibodies that reacted with GD1b containing a NeuNAc(α2‐8)NeuNAc(α2‐3)Gal epitope localized on the cell bodies of human dorsal root ganglia 8, 10.…”
mentioning
confidence: 99%